악교정수술 전후의 하악하연 피질골 두께 비교연구 - 윤숙자; 이은주; 김성진; 강병철; 이재서 (대한구강악안면병리학회지, 41(1), 2017)
The purpose of this study is to evaluate the clinical and radiographic features of Bisphosphonate-related osteonecrosis of the jaws(BRONJ). The clinical and radiographic features of 27 patients diagnosed with BRONJ from 2008 to 2012 were evaluated on the basis of the charts and panoramic radiographs and cone beam computed tomographs. As for clinical features, the following contents were evaluated; type of dental treatments before occurrence of BRONJ, the cause of taking bisphosphonate medicine, undergoing dental treatment, interval between dental treatments and symptom expression. As for radiological features, location of BRONJ, size of bone destructions and sclerosing of the surrounding bone, locational relationship between mandibular canal and inferior border of bone destruction, and effect on the maxillary sinus. In clinical features, extraction was done in 18 patients(66.7%), as the most common dental treatment before occurrence of BRONJ. The most common cause of taking bisphosphonate medicine was osteoporosis(20 pateints, 70.4%). The patients treated during bisphosphonate administration was 17(63.0%). The interval between dental treatments and symptom in the most patients(14 patients, 51.8%) was within 1 month. In radiological features, sequestrum was seen in 11 patients(40.7%) and bony sclerosing in 15(55.6%). The mean width of sclerosing was 32.9±12.4mm and mean height 17.5±4.4mm. Bone destruction invaded to inferior border of mandibular canal in 88.2%(15 among 17 mandibles),. Maxillary sinusitis was diagnosed in 57.1% among the evaluated maxillae(4 among 11 maxillae). In diagnosing BRONJ, clinicians should be cautious about medical history of patients and have well-knowledge of radiographic features. KCI Citation Count: 0